Acute high-intensity interval exercise is superior to moderate-intensity continuous exercise in enhancing endothelial function and its associated biomarkers in sedentary young individuals: the possible involvement of lactate - Ziqing Liu; Jinglin Huang; Min Hu; Xuyan Cui; Lu Leng; Kangle Wang; Jiarui Wu; Shan He; Weiji Deng; Peilun Li; Yilin Chen; Dongdong Gao; et al. (Journal of Exercise Science & Fitness)
Abstracts: Objectives: Our study investigated the effects of acute high-intensity interval exercise (HIIE) and moderate-intensity continuous exercise (MICE) on endothelial function and its associated biomarkers in sedentary young individuals. Methods: Fifteen subjects (10M / 5F; 22 ± 2 years; BMI: 23.07 ± 4.12 kg/m2) participated in a crossover trial including three experimental conditions: HIIE, MICE, and a control session of rest (CON) in random order separated by a 7-day washout period. Endothelial function was assessed using flow-mediated dilation (FMD), mean shear rate (MSR), and circulating levels of blood lactate, VEGF, IGF-1, and irisin. Results: Both HIIE and MICE significantly enhanced FMD% (both P < 0.001 and P < 0.01, respectively), lactate (both P < 0.001), VEGF (P < 0.001 and P < 0.01, respectively), IGF-1 (both P < 0.001), and irisin (P < 0.001 and P < 0.05, respectively), with a greater extent after HIIE compared to MICE in FMD% (P < 0.001), MSR (P < 0.05), lactate (P < 0.001), VEGF (P < 0.05), and IGF-1 (P < 0.05). Additionally, change (post-pre) in FMD% was positively correlated with changes in MSR, lactate, and VEGF in both HIIE and MICE conditions. Change in MSR was positively associated with changes in lactate and VEGF in both HIIE and MICE conditions. Furthermore, enhancement in lactate was correlated with enhancements in VEGF in both HIIE and MICE conditions. Conclusions: Acute HIIE is a more effective method than MICE at improving endothelial function in sedentary young individuals and increases in lactate and its mediated VEGF release, attributed to increase in shear rate after exercise, are involved in regulatory mechanisms.